Geographical analysis of the type and age composition of the population of Sulaimani province between the years (1977-2012). - حەمە, سروە جەلال (Sulaimani Journal for Humanities, 2019)
The age and Quality structures in the Province of Sulaimany in the period (1977-2012) represents a special importance due to their effect and efficacy on some demographic standards such as births, deaths and migrations .The current Study aims at pinpointing the changes on both structures mentioned between (1977-2012).The study found out some results , the most important one of them is the high rate of quality in Sulaimany province. in 1977 it amounted to (118.8%) (male/100 female), thus reaching its zenith. While in 1987 it amounted to (103.1%) (male/100female).As far as the year 2012 is concerned the rate went down to (100.1%) on the level of the Province . With respect to the age structure of population on the level of the Province, it as well changed on account of so many factors, demographic, social and political. Regarding the dependency ratio , the general trend of the total of dependency ratio on the level of the province (rural and urban areas) it tended downwards at the end of the study period as compared to its start .